Estimated protective effectiveness of intramuscular immune serum globulin post-exposure prophylaxis during a measles outbreak in British Columbia, Canada, 2014. Issue 20 (9th May 2017) - Bigham, Mark; Murti, Michelle; Fung, Christina; Hemming, Felicity; Loadman, Susan; Stam, Robert; Van Buynder, Paul; Lem, Marcus
Highlights: In this measles outbreak, estimated crude protective effectiveness of IM ISG PEP was 69%. This estimate was vulnerable to uncertainties in ascertaining immune status and exposure details. An IM ISG PEP dose of 0.5 ml/kg (maximum volume 15 ml) may improve protective effectiveness. Abstract: Introduction: Intramuscular Immune Serum Globulin (IM ISG) is recommended as post-measles exposure prophylaxis (PEP) when administered within 6 days of initial exposure, with variable effectiveness in preventing measles disease. Effectiveness of IM ISG PEP in preventing clinical measles was assessed during a 2014 measles outbreak among a religious-affiliated community in British Columbia, Canada. Material and methods: Fifty-five self-reporting measles susceptible contacts were offered exclusively IM ISG PEP within an eligibility period best surmised to be within 6 days of initial measles case exposure. Clinical outcome of IM ISG PEP recipients was determined by selective active surveillance and case self-reporting. IM ISG PEP failure was defined as onset of a measles-like rash 8–21 days post-IM ISG PEP. Post-IM ISG PEP measles IgG antibody level was tested in 8 recipients. Factors associated with measles disease were analyzed. Results: Seventeen of 55 IM ISG PEP recipients developed clinically consistent measles in the following 8–21 days, corresponding to an estimated crude protective effectiveness of 69%. In school aged children 5–18 years, among whom potential exposure intensity and immune status confounders were considered less likely, estimated IM ISG PEP protective effectiveness was 50%. Age <25 years was significantly associated with breakthrough clinical measles in bivariate analysis (p = 0.0217). Among 8 tested contacts of 17 considered IM ISG PEP failures, post-IM ISG PEP measles IgG antibody levels (mean 16.3 days (range 16–17 days) post-PEP) were all <150 mIU/ml. Conclusions: The estimated crude IM ISG PEP protective effectiveness against measles disease within 8–21 days post-ISG administration was 69%. Accuracy of this estimated protective effectiveness is vulnerable to assumptions and uncertainties in ascertaining exposure details and pre-exposure immune status. Increasing the Canadian recommended measles IM ISG PEP dose from 0.25 to 0.5 ml/kg (up to 15 ml maximum volume) may increase protective effectiveness.